Estimation of the effect of Tsallis non-extensive statistics on the 14C(n,γ)15C reaction rate - Tkachenko, A. S.; Burkova, N. A.; Yeleusheva, B. M.; Dubovichenko, S. B. (Frontiers in Physics, 2025)
The total cross-section of the radiative neutron capture reaction 14С(n,γ0+1)15C—for energies ranging from 10 meV to 5 MeV—is considered. Calculations performed in the framework of the modified potential cluster model with forbidden states show an agreement of total cross-section σ (23.3 keV) = 4.75 μb with the presently recommended value 4.86(48) μb by Ma et al., 2020. The efficiency of carbon isotope 15C production is illustrated by the 14С(n,γ0+1)15C reaction rate calculated at temperatures from T9 = 0.001 to T9 = 10. The conventional Maxwell–Boltzmann weighted reaction rate σvMB of the present work is comparable, with less than 10% accuracy, with the latest calculations by Ma et al., 2020 and Bhattacharyya et al., 2021. The estimation of non-extensive effects is implemented using our data on the reaction rate σvMB as reference values. The efficiency of carbon isotope production in radiative capture reactions 12-14С(n,γ)13-15C is estimated based on the calculated reaction rates. The influence of the Maxwellian-weighted 12-14C(n,γ)13-15C reaction rates on the ratios 12C/13C and 13C/14C is examined. Tsallis statistics is applied for the first time to the calculation of the 14С(n,γ0)15C reaction rate with values of non-extensive parameter 0.7 ≤ q ≤ 1.3 on the background of Maxwell–Boltzmann statistics corresponding to q = 1. The reaction rate σvq shows a factor ∼4 increase for q = 0.7 and a factor ∼0.6 decrease for q = 1.3 compared to q = 1.